The judicialization of politics in Asia - Dressel, Björn (Routledge law in Asia ;, 2012)
"Over the last two decades courts have become major players in the political landscape in Asia. This book assesses what is driving this apparent trend toward judicialization in the region. It looks at the variations within the judicialization trend, and how these variations affect political practice and policy outcomes."--Publisher's description.